Exploring the Integration of Technology in English Language Teaching: A Research Study - Mardiana, Harisa (Pusat Penelitian dan Pengabdian Masyarakat STIKes Banyuwangi, 2024)
Exploring the Integration of Technology in English Language Teaching: A Research Study, investigates the multifaceted relationship between technology and English language instruction. This mixed-methods study delves into English language teachers' attitudes, practices, challenges, and aspirations regarding technology integration. A combination of quantitative surveys and qualitative interviews, the study examines the perceptions and experiences of educators at varying levels of technology integration proficiency. Quantitative analyses reveal mean scores and frequencies across dimensions such as technology's role, integration challenges, perceived benefits, and impact on student engagement and learning outcomes. Qualitative provides depth and context, elucidating individual experiences, strategies, and visions for the future. Convergence and divergence between quantitative data and qualitative narratives offer nuanced understandings of technology integration in language education. Findings indicate a generally positive attitude towards technology integration among participants, tempered by challenges such as technical proficiency, resource accessibility, and pedagogical alignment. Despite obstacles, the teachers express a collective vision for technology's transformative potential in language teaching, advocating for innovation, equity, and student-centered learning. The study contributes to the ongoing discourse on technology integration in language education, offering insights for policymakers, practitioners, and researchers striving to harness the benefits of technology for enhanced language learning experiences.